Spatial Release from Masking with a Moving Target - Pastore, M. Torben; Yost, William A. (Frontiers in Psychology, 2017)
In the visual domain, a stationary object that is difficult to detect usually becomes far more salient if it moves while the objects around it do not. This ``pop out'' effect is important for parsing the visual world into figure/ground relationships that allow creatures to detect food, threats, etc. We tested for an auditory correlate to this visual effect by asking listeners to identify a single word, spoken by a female, embedded with two or four masking words spoken by males. Percentage correct scores were analyzed and compared between conditions where target and maskers were presented from the same position versus when the target was presented from one position while maskers were presented from different positions. In some trials, the target word was moved across the seaker array using amplitude panning, while in other trials that target was played from a single, static position. Results showed a spatial release from masking for all conditions where the target and maskers were not located at the same position, but there was no statistically significant difference between identification performance when the target was moving versus when it was stationary. These results suggest that, at least for short stimulus durations (0.75 s for the stimuli in this experiment), there is unlikely to be a ``pop out'' effect for moving target stimuli in the auditory domain as there is in the visual domain.